TINJAUAN YURIDIS MENGENAI HAK IMUNITAS SEORANG ADVOKAT YANG MELAKUKAN TINDAKAN OBSTRUCTION OF JUSTICE DALAM PERKARA KORUPSI (CONTOH PUTUSAN NOMOR 90/Pid.Sus-TPK/2018/PN.Jkt.Pst) - Sri Ayu Sukmawati Loi; Dian Adriawan DG Tawang (Jurnal Hukum Adigama, 2020)
Advocates have immunity rights that cannot be prosecuted either by civil law or crimes to uphold justice for their clients, therefore this research is to submit an application for advocate's immunity rights under Article 16 of the Advocate Law relating to work agreements and employment assistance for obstruction of legal protection. The research method used is normative legal research. The results of the analysis in this study are that the application of advocacy protection rights only applies to advocates who have legal relations with the people they help (clients) and facilitate their profession to support their clients in good faith to uphold in accordance with appropriate laws. Judicial practices Barring justice in corruption cases under Article 21 UUPTPK is another crime related to corruption but not corruption which is a general crime, which is related to conducting investigations and prosecutions is the police and prosecutors, not the KPK. It is unfair if the KPK becomes a victim of an objection to justice and at the same time acts as a law enforcer. Provisions Regarding Barriers to Regional Regulation Article 221 of the Criminal Code, Article 21 of Law Number 31 of 1999 Jo. Law Number 20 of 2001 concerning Corruption Eradication, Article 20 to Article 24 of Law Number 21 of 2007 TPPO and also regulated in Article 25 of the United Nations Convention Against Corruption (UNCAC).